2022
DOI: 10.1093/jisesa/ieac047
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genes in Regulating Host Plants Expansion in Tephritid Fruit Flies (Diptera) and Potential for RNAi-Based Control

Abstract: Host plant expansion is an important survival strategy for tephritids as they expand their range. Successful host expansion requires tephritids to adapt to the chemical and nonchemical properties of a novel host fruit, such as fruit color, phenology, and phytochemicals. These plant properties trigger a series of processes in tephritids, with each process having its own genetic basis, which means that various genes are involved in regulating host plant expansion by tephritids. This review summarizes current kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 122 publications
1
3
0
Order By: Relevance
“…This aligns with the results of Shi et al. ( 2022 ) and a recent study that showed increased ORs in generalist B. dorsalis when compared to specialist B. minax (Wang et al., 2022 ). However, the number of GRs and OBPs were not significantly different (GR: H 2,12 = 0.485, p = 0.785; OBP: H 2,24 = 2.563; p = 0.277) (Figure 4 ).…”
Section: Case Study 3 Comparison Of Generalists Versus Specialists Wi...supporting
confidence: 92%
See 2 more Smart Citations
“…This aligns with the results of Shi et al. ( 2022 ) and a recent study that showed increased ORs in generalist B. dorsalis when compared to specialist B. minax (Wang et al., 2022 ). However, the number of GRs and OBPs were not significantly different (GR: H 2,12 = 0.485, p = 0.785; OBP: H 2,24 = 2.563; p = 0.277) (Figure 4 ).…”
Section: Case Study 3 Comparison Of Generalists Versus Specialists Wi...supporting
confidence: 92%
“…Shi et al. ( 2022 ) also reported a greater number of cytochrome P450s in the polyphagous B. dorsalis and C. capitata than in the monophagous B. oleae .…”
Section: Case Study 3 Comparison Of Generalists Versus Specialists Wi...mentioning
confidence: 93%
See 1 more Smart Citation
“…In total, the 14 combinations selected involved eight ORs and four odorants (1-octen-3-ol (Oct-3OL), LIN, ME, and EOL) (Figure S8). Two of the ORs, BmOR13a1 and BdOR13a1, were orthologs in the two species 53 .…”
Section: Hydrophobicity-based Msas Of Key Helices For the Tbmmentioning
confidence: 99%